PENGARUH MEDIA POSTER TEMPEL TERHADAP PERILAKU PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA WANITA BERESIKO - Wike Rosalini; Lailil Fatkuriyah; M. Elyas Arif Budiman; Irwina Angelia Silvanasari (PROFESSIONAL HEALTH JOURNAL, 2023)
One of the health problems faced by women is breast cancer, breast cancer is the most common cancer worldwide and the second cancer that causes death. Breast cancer is the most common in women, namely 42.1 per 100,000 population. Breast cancer can be detected early by breast self-examination or BSE, but many women forget the method and order of practice. Using posters can provide reminders and ways for women to continue doing BSE. This type of research is a quasi-experimental quantitative research. The research design used was a pretest-posttest control group design. The results show differences in knowledge, attitudes and practices each and between groups. Knowledge attitudes and practices have improved overall since the intervention. At the end of the measurement, all groups had good BSE knowledge and attitudes. Behavior with good category before treatment 18% to 39%. In conclusion there are differences in knowledge, attitudes and practices respectively and between groups. Poster media is an effective medium for increasing knowledge and practice. Posted poster media is effective in increasing BSE attitude.